The genomic landscape of pediatric myelodysplastic syndromes - Schwartz, Jason R.; Ma, Jing; Lamprecht, Tamara; Walsh, Michael; Wang, Shuoguo; Bryant, Victoria; Song, Guangchun; Wu, Gang; Easton, John; Kesserwan, Chimene; Nichols, Kim E.; Mullighan, Charles G.; et al. (Nature communications, 2017)
Myelodysplastic syndromes (MDS) are uncommon in children and have a poor prognosis. In contrast to adult MDS, little is known about the genomic landscape of pediatric MDS. Here, we describe the somatic and germline changes of pediatric MDS using whole exome sequencing, targeted amplicon sequencing, and/or RNA-sequencing of 46 pediatric primary MDS patients. Our data show that, in contrast to adult MDS, Ras/MAPK pathway mutations are common in pediatric MDS (45% of primary cohort), while mutations in RNA splicing genes are rare (2% of primary cohort). Surprisingly, germline variants in SAMD9 or SAMD9L were present in 17% of primary MDS patients, and these variants were routinely lost in the tumor cells by chromosomal deletions (e.g., monosomy 7) or copy number neutral loss of heterozygosity (CN-LOH). Our data confirm that adult and pediatric MDS are separate diseases with disparate mechanisms, and that SAMD9/SAMD9L mutations represent a new class of MDS predisposition. Myelodysplastic syndromes (MDS) are uncommon in children and have poor prognosis. Here, the authors interrogate the genomic landscape of MDS, confirming adult and paediatric MDS are separate diseases with disparate mechanisms, and highlighting that SAMD9/SAMD9L mutations represent a new class of MDS predisposition.